Incisional carcinoma of Mullerian Origin: A case report and review of literature - Sabrina Bedell; Zenas Chang; Cassaundra Burt; Mahmoud A. Khalifa; Peter A. Argenta (Elsevier, 2020)
Primary incisional carcinoma (PIC) is a rare, delayed complication of surgery, usually attributed to the malignant transformation of endometriosis.We report a case of incisional carcinoma with nodal metastases in a 55-year-old woman, 18 years after cesarean section. She underwent extirpative surgery, including hysterectomy and bilateral salpingo-oophorectomy, without intraperitoneal disease identifed. Adjuvant treatment included sandwiched platinum-based chemotherapy (carboplatin and paclitaxel) and radiation. She remains disease-free 8 months after completing therapy.We identified 46 additional reported cases. Of these, >90% had undergone an "endometrium-exposing" surgery, most commonly cesarean section; while no cases followed adnexal-only surgery. The median time between antecedent surgery and presentation was 18 years. At presentation, tumors were often large (median 8 cm), and symptomatic with pain (63%) and/or mass (26%). Serum CA125 levels were commonly, albeit slightly, elevated (median 57U/ml (IQR 22-96, Range 6-1690)). Lymph node metastases were common (35%), with most following a vulvar-type spread pattern (inguinal first). Most patients (63%) were treated with chemotherapy +/− radiation. Approximately 50% of patients recurred promptly (median < 6 months), but long-term survival was reported following combined chemotherapy/radiation. Lymph node metastases portended a shorter disease-free interval, with 73% of cases recurring (median 5 months) despite chemotherapy-based treatment.These data suggest that some incisional carcinomas may result from displacement of healthy endometrium followed by delayed malignant transformation. Chemotherapy-only and radiation-only treatments are attended by modest prognosis. Taken together, these data suggest there is both need and potential avenues for improved prevention, detection, and treatment of this condition.